Efficient method for isolation of high-quality RNA from Psidium guajava L. tissues. - Paola de Avelar Carpinetti (Public Library of Science (PLoS), 2021)
Acquiring high-quality RNA in sufficient amounts is crucial in plant molecular biology and genetic studies. Several methods for RNA extraction from plants are available in the literature, mainly due to the great biochemical diversity present in each species and tissue, which can complicate or prevent the extraction. Psidium guajava (Myrtaceae family) is a perennial fruit tree of medicinal and economic value; nevertheless, only a few molecular studies are available for the species. One reason is the difficulty in obtaining RNA due to the content of the samples, which are rich in polyphenols, polysaccharides, and secondary metabolites. Furthermore, there are few studies available for the isolation of RNA from guava or Psidium samples, which hampers advances in the study of the genus. Here, quality and yields of RNA isolates were compared using six extraction protocols: two protocols based on the application of cetyltrimethylammonium bromide (CTAB) lysis buffer, one protocol which uses the TRIzol reagent, one which applies guanidine thiocyanate lysis buffer followed by organic phase extraction, and two commercial kits (PureLink RNA Mini Kit and RNeasy Plant Mini Kit). The CTAB-based method provided the highest RNA yields and quality for five different tissues (flower bud, immature leaf, young leaf, mature leaf, and root), genotypes, and stress conditions. For the most efficient protocol, the average yield of RNA from guava leaves was 203.06 μg/g of tissue, and the A260/A280 and A260/A230 ratios were 2.1 and 2.2, respectively. RT-qPCR analysis demonstrated that the purity of the samples was sufficient for molecular biology experiments. CTAB-based methods for RNA isolation were found to be the most efficient, providing the highest RNA yields and quality for tissues from P. guajava. Additionally, they were compatible for downstream RNA-based applications, besides being simple and cost-effective.